Sevoflurane as the Single Anesthetic Agent for Management of Anticipated Pediatric Difficult Airway - Roodneshin, Fatemeh (National Research Institute of Tuberculosis and Lung Disease, 2012)
Mucopolysaccharidoses (MPSs) are a group of hereditary diseases characterized by accumulation of Glycosaminoglycans (GAGs) due to deficiency or malfunctioning of lysosomal enzymes. Difficult intubation is anticipated in these patients because of a variety of anatomical and functional abnormalities. We report the successful use of sevoflurane and laryngeal mask for airway management of a 15 year-old boy requiring corneal transplantation surgery.